Manufacturing Digitalization Promoting Social Sustainability Based Competitiveness : Case: UPM Raflatac - Tempakka, Severi (My University, 2023)
In today's dynamic world, businesses strive to leverage cutting-edge technological advancements, with digitalization transforming various aspects of society. This shift raises crucial questions about the role of humans in a society where machines are replacing repetitive tasks. A key concern is the lack of understanding regarding social sustainability, as its integration into the digitalization process is vital to avoid potential broader societal problems. This research aims at striking a balance between addressing social sustainability concerns and maintaining competitiveness within companies. The central objective is to explore how digitalization, specifically the transition from Industry 4.0 to Industry 5.0, can promote social sustainability and thereby enhance competitiveness, enabling businesses to remain successful in the market. The research question examines how digitalization in manufacturing (I4.0 to I5.0) can endorse social sustainability-based competitiveness. This involves two sub-questions: understanding the link between digitalization and social sustainability in manufacturing and identifying how social sustainability promotes competitiveness. The study draws on academic literature and empirical data from a chosen case company, collected through 7 semi-structured interviews and analysed using the Gioia method. The chosen case company, UPM Raflatac, is a global labelling material manufacturer, recognized for its commitment to sustainability and innovation within the label industry. The findings align with existing literature, revealing that social sustainability isn't easily tied to economic success. Industry 4.0 emphasizes global competitiveness, while I5.0 addresses broader sustainability concerns. The study identifies three chains through which digitalization in manufacturing endorses social sustainability, resulting in competitive advantages. 1. digitalization supports social and environmental sustainability, seen as essential for competitiveness and future business success, 2. manufacturing digitalization improves stakeholder relations, enhancing reputation and social sustainability benefits, 3. digitalization drives economic prosperity, enabling social sustainability and the growth of intellectual capital. The conclusions drawn are based on a synthesis of empirical data and corroborated by insights from existing literature. The results are limited to the singular case company, constraining their generalizability to that specific context and business domain.

Nykypäivän nopeasti muuttuvassa maailmassa yritykset pyrkivät hyödyntämään huipputeknologian edistysaskeleita samalla, kun digitalisaatio muuttaa yhteiskunnan lukuisia eri osa-alueita. Muutokset herättävät tärkeitä kysymyksiä ihmisten roolista yhteiskunnassa, jossa koneet korvaavat yhä useampia toistuvia tehtäviä. Keskeinen huolenaihe on ymmärryksen puute liittyen sosiaaliseen kestävyyteen, jonka integroiminen digitalisaatioprosessiin on välttämätöntä mahdollisten laajempien yhteiskunnallisten ongelmien välttämiseksi. Tämän tutkimuksen tavoitteena on löytää tasapaino sosiaalisen kestävyyden huomioimisen ja yritysten kilpailukyvyn ylläpitämisen välillä. Keskeisenä tavoitteena on selvittää, miten digitalisaatio, erityisesti siirtyminen Industry 4.0:sta Industry 5.0:aan, voi edistää sosiaalista kestävyyttä ja sitä kautta parantaa kilpailukykyä, mikä puolestaan mahdollistaa yritysten menestymisen markkinoilla. Tutkimuskysymyksessä tarkastellaan miten tuotannon digitalisaatio (I4.0 - I5.0) voi tukea sosiaaliseen kestävyyteen perustuvaa kilpailukykyä. Tähän liittyy kaksi alakysymystä: digitalisaation ja tuotannon sosiaalisen kestävyyden välisen yhteyden ymmärtäminen ja sen tunnistaminen, kuinka sosiaalinen kestävyys edistää kilpailukykyä. Tutkimus pohjautuu akateemiseen kirjallisuuteen ja tutkimuksen kohteeksi valitun yrityksen empiiriseen dataan, joka on kerätty seitsemällä puolistrukturoidulla haastattelulla ja analysoitu Gioia-menetelmällä. Valittu tapaustutkimuksen yritys, UPM Raflatac, on maailmanlaajuinen etikettimateriaalien valmistaja, joka on tunnustettu sitoutumisestaan kestävään kehitykseen ja innovaatioihin tarrateollisuudessa. Tutkimuslöydökset, jotka ovat yhdenmukaisia olemassa olevan kirjallisuuden kanssa, osoittavat, että sosiaalinen kestävyyden ja taloudelliseen menestyksen välisen yhteyden todentaminen on haastavaa. Industry 4.0 korostaa globaalia kilpailukykyä, kun taas I5.0 käsittelee laajempia kestävyysnäkökohtia. Tutkimuksessa tunnistetaan kolme syy-seuraus toimintamallia, joiden kautta tuotannon digitalisaatiolla voidaan tukea kilpailuetuun johtavaa sosiaalista kestävyyttä. 1. digitalisaatio tukee sosiaalista ja ympäristön kestävyyttä, jota pidetään välttämättömänä kilpailukyvyn ja tulevan liiketoiminnan menestyksen kannalta. 2. tuotantoalan digitalisaatio parantaa sidosryhmien suhteita, lisää mainetta ja sosiaalisen kestävyyden etuja, 3. digitalisaatio edistää taloudellista hyvinvointia mahdollistaen sosiaalisen kestävyyden ja osaamispääoman kasvun. Tehdyt johtopäätökset perustuvat empiiristen tietojen synteesiin, ja niitä tukevat olemassa olevan kirjallisuuden oivallukset. Tulokset koskevat yksittäistä tutkimuksen kohteena ollutta yritystä, mikä rajoittaa niiden yleistettävyyden kyseiseen kontekstiin ja liiketoiminta-alueeseen.
Keywords: Industry 4.0, Industry 5.0, Social Sustainability